Perancangan Logo dan Media Promosi Pulau Mengare Gresik Berbasis Edukasi Sebagai Upaya Mengenalkan Wisata Sejarah - Putri, Dinda Cholifah; Bahruddin, Muhammad; Khoiriqqoh, Abdullah (Jurnal Art Nouveau, 2016)
The purpose of designing this Mengare Island media campaign is to introduce and preserve the historical heritage Mengare . The study was conducted using qualitative research is to conduct interviews , observation , documentation , and literature to obtain data to support the drafting . Data were analyzed using multiple stages of data reduction , data presentation and conclusion. From these results we found the concept of " Enjoy Life With Adventure " which is a pleasant journey . In this case how to preserve historical heritage by making sites that are promoted with the right strategy to the target audience . The design of the work refers to the principles of design and how to create a media campaign in accordance with the design consistency . The results of the design is expected to add excursions .Â Keywords: Design , Media Campaign , Mengare Island , History , Culture